2014
DOI: 10.1002/ar.23029
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Morphometry in Marmosets: Loss and Redistribution of Olfactory Surface Area

Abstract: The two major groups of primates differ in internal nasal anatomy. Strepsirrhines (e.g., lemurs) have more numerous turbinals and recesses compared with haplorhines (e.g., monkeys). Since detailed quantitative comparisons of nasal surface area (SA) have not been made, we measured mucosa in serially sectioned monkeys (Callithrix jacchus, Cebuella pygmaea). Data were compared with previously published findings on the mouse lemur, Microcebus murinus. The nasal airways were digitally reconstructed using computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…b. The lateral recess (pink color) is fitted compactly between the MT and ET, in contrast to the outwardly protruding recess in deer (Ranslow et al, ), Marmosets (Smith et al, ), and humans (Xi et al, c). The nasal septum ends at the NM region and the two nasal passages merge at the anterior point (approximately 43.0 mm from the naris) of the ET region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…b. The lateral recess (pink color) is fitted compactly between the MT and ET, in contrast to the outwardly protruding recess in deer (Ranslow et al, ), Marmosets (Smith et al, ), and humans (Xi et al, c). The nasal septum ends at the NM region and the two nasal passages merge at the anterior point (approximately 43.0 mm from the naris) of the ET region.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, MRI performs better than CT in resolving the interface of air and soft‐tissues (De Rycke et al, ). To date, only a few studies reported detailed regional morphometric data for dogs (Craven et al, ), deer (Ranslow et al, ), marmosets (Smith et al, ), and humans (Orhan et al, ; Xi et al, ). Moreover, few studies considered the morphometry of the rabbit nasal airway.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al () found an interesting difference in the distribution of OE between two marmoset species ( Callithrix jaachus , Cebuella pygmaea ) and the lesser mouse lemur ( Microcebus murinus ). Both of the marmosets had more than 70% of their OE located on surfaces other than the ethmoturbinals, such as paranasal spaces and the septum.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of mean percentage of total nasal fossa area covered by olfactory epithelium in seven mammalian orders. Data are from the four focal species used in this study as well as from Smith et al (2012Smith et al ( , 2014.…”
Section: Comparisons With Other Mammalsmentioning
confidence: 99%
See 1 more Smart Citation